Sex difference in cold perception and shivering onset upon gradual cold exposure. (October 2018) - Kaikaew, Kasiphak; van den Beukel, Johanna C.; Neggers, Sebastian J.C.M.M.; Themmen, Axel P.N.; Visser, Jenny A.; Grefhorst, Aldo
Abstract: To maintain a thermal balance when experiencing cold, humans reduce heat loss and enhance heat production. A potent and rapid mechanism for heat generation is shivering. Research has shown that women prefer a warmer environment and feel less comfortable than men in the same thermal condition. Using the Blanketrol ® III, a temperature management device commonly used to study brown adipose tissue activity, we tested whether the experimental temperature ( T E ) at which men and women start to shiver differs. Twenty male and 23 female volunteers underwent a cooling protocol, starting at 24 °C and gradually decreasing by 1–2 °C every 5 min until an electromyogram detected the shivering or the temperature reached 9 °C. Women started shivering at a higher T E than men (11.3 ± 1.8 °C for women vs 9.6 ± 1.8 °C for men, P  = 0.003). In addition, women felt cool, scored by a visual analogue scale, at a higher T E than men (18.3 ± 3.0 °C for women vs 14.6 ± 2.6 °C for men, P  < 0.001). This study demonstrates a sex difference in response to cold exposure: women require shivering as a source of heat production earlier than men. This difference could be important and sex should be considered when using cooling protocols in physiological studies. Highlights: Women start shivering at a higher experimental temperature than men. Women feel colder and less comfortable than men during the same cooling protocol. Thermal perception at room temperature and sex are determinants of shivering onset. Sex of a participant should be considered for thermoregulation studies.